Manajemen Produksi Program Podcast “Ngobrol Lingkungan” pada Kanal YouTube Greenpeace Indonesia - Farrel Wiratama Raisyah Nurman; Hadiyanto Hadiyanto; Enden Darjatul Ulya (Jurnal Riset Rumpun Seni, Desain dan Media, 2026)
The growth of digital media consumption has propelled YouTube to become an important platform for environmental campaign organizations such as Greenpeace Indonesia to disseminate information through various content formats, including podcasts. The Ngobrol Lingkungan podcast program aims to explore environmental issues in depth through focused conversations. This study aims to explain the management of podcast production using the POAC framework, which includes planning, organizing, executing, and controlling, as well as identifying obstacles that arise at each stage of production. The study uses a descriptive qualitative approach with primary data in the form of observations of the production workflow and semi-structured interviews with the production team, as well as secondary data from supporting documents and literature. Data collection was conducted from August to October 2025. The research results are expected to map production practices at each stage, identify technical and non-technical obstacles and their impact on process continuity and output quality, and produce concrete recommendations for improving future episodes. These findings are expected to enrich the study of POAC-based podcast production management and provide practical guidance for similar programs in campaign or public education organizations.